Generic communication requirements of ITS-related mobile services as basis for seamless communications - Fiedler, M.; Chevul, S.; Isaksson, L.; Lindberg, P.; Karlsson, J. (2005 Next Generation Internet Networks, 2005)
In order to meet user expectations and to be of efficient help for people using or implementing Intelligent Transport Systems and Services (ITS), mobile ITS-related services need efficient support from the underlying communication systems, which in turn requires profound knowledge of those needs. As a first step towards an optimal automatic choice of communication technologies in order to provide for seamless communications, this paper groups services into generic groups and presents a framework to classify their needs in terms of availability, performance, security and cost in a generic manner. These needs are consequently seen from the user's perspective, but formulated in a way such that they can be matched towards known network parameters. Upon comparing needs with offers, the feasibility of a certain communication technology for a certain type of service can be determined both proactively and reactively, which helps to automatically select the right kind of connectivity in order to yield the desired degree of availability, performance, security and cost. We motivate for instance the need for determining and monitoring application-perceived speeds, a multi-level security models and the one-stop service concept. We also provide an example on how these needs can be matched to offers by different networks.